Role of metabolic reprogramming and lactylation in diabetic nephropathy: molecular mechanisms and therapeutic prospects – a narrative review - Li, Zongtao; Wang, Yashi; Fang, Die; Ye, Wenfeng; Zhang, Xueqin; Chen, Zhiqiang (Frontiers in Endocrinology, 2026)
Diabetic nephropathy (DN) remains challenging to halt completely despite standard therapies. Beyond being a glycolytic byproduct, lactate can act as a signaling metabolite and a substrate for lysine lactylation, linking metabolic reprogramming to chromatin regulation. To summarize the lactate–lactylation axis in DN and its translational implications, we conducted a narrative review by searching PubMed, Web of Science, and Scopus for English-language studies up to October 2025 using terms related to DN, metabolic reprogramming, glycolysis, lactate, and lactylation. Evidence was prioritized from DN/kidney studies, with selected mechanistic reports from related contexts included when relevant. The results show that hyperglycemia, hypoxia, and inflammation promote a shift toward glycolysis, leading to lactate accumulation, mitochondrial dysfunction, and inflammatory signaling in DN. Lactate-associated histone and non-histone lactylation has been implicated in cell-type–dependent transcriptional programs across tubular epithelial cells, podocytes, endothelial cells, and immune cells, potentially amplifying inflammation and fibrosis. Candidate “writers/erasers” and emerging non-canonical lactyltransferase activities suggest lactylation may represent a tunable epigenetic node. Thus, the lactate–lactylation axis provides a promising but evolving framework for DN pathogenesis and therapy. Future work should prioritize DN-focused validation, including studies using human DN samples where feasible, standardized detection, and stage- and cell-specific interventions to minimize systemic metabolic disruption.